Pollen movement in a Malus sylvestris population and conclusions for conservation measures. Issue 1 (14th August 2015) - Reim, Stefanie; Proft, Anke; Heinz, Simone; Lochschmidt, Frank; Höfer, Monika; Tröber, Ute; Wolf, Heino
Abstract : Knowledge of pollen movement and frequency of interspecific hybridization in fragmented populations of rare species is a prerequisite for the implementation of conservation measures. In a large-scale study area (14, 000 hectares) we analysed 297 Malus sylvestris trees with nine nuclear microsatellite markers. After open pollination of 564 offspring from 51 mother trees located in seven harvesting sites were investigated and genetic paternity analysis was performed. The paternal parent was identified for 213 offspring and the pollen dispersal distances between mother and pollen source were calculated. A large proportion of detected pollination events (42.4%) were observed within a radius of 50 m of the mother tree. The comparison of different tree densities indicated that with decreasing density the pollen dispersal distances increase. We observed pollination over long distances with a maximum of 10.7 km which is probably one of the reasons for a low spatial genetic structure within the M. sylvestris population and a stable genetic diversity in the offspring. Incorporating microsatellite data of 21 apple cultivars, a hybridization frequency of nearly 8% was determined. With decreasing tree density the number of hybridization events increased. Based on the results of our study an enhancement of the density of existing M. sylvestris populations is recommend to reduce the likelihood of hybridization. The production of young plants originated from seeds collected after open pollination is not advisable. Instead of that the seedlings for further reintroduction measures should be produced by controlled crossings in seed orchards to ensure 'true type' M. sylvestris individuals.